Position-related somatotype of elite female handball players - Petkovic, E.; Bubanj, S.; Markovic, K.; Kocic, M.; Stankovic, D. (Acta facultatis medicae Naissensis, 2019)
Anthropometric characteristics and motor abilities are the most influential factors for the achievement of top sports results. The sample of participants consisted ofelite female handball players (n=19, mean age: 27.67 years ± 6 months), the members of the Serbian senior national team. In this research, their body constitution, i.e. their somatotype was studied. The somatotype was determined according to the methodology of Heath-Carter, using the computer software Somatotype 1.2. The statistical analysis of the results was performed using Statistics v.10. The prevailing somatotype among the female handball players in all positions is the mesomorph somatotype. The obtained results are consistent with the aforementioned characteristics of the mesomorph type conditioned by the specific requirements of the game of handball. Each handball player developed their own musculature and strengthened their skeletal-joint system owing to the contact game and the movements that handball requires.